Prevalence of Serous Tubal Intraepithelial Carcinoma (STIC) at the Time of Postpartum Contraceptive Procedures during Caesarean Delivery - Sara Forte; Giorgia Mazzoni; Federico Ferrari; Laura Ardighieri; Gaetano Valenti; Enrico Sartori; Franco Odicino (Clinical and Experimental Obstetrics & Gynecology)
Background: To assess the prevalence of serous tubal intraepithelial carcinoma (STIC) in women underwent opportunistic salpingectomy at the time of caesarean delivery (CD). Methods: We conducted a retrospective cohort study (2014–2017) of women who received either bilateral total or partial salpingectomy as postpartum permanent contraception procedure during CD. We collected the characteristics of the patients, the type of CD (elective versus unscheduled), the type of surgical procedure and the related complications. We analysed surgical outcomes and calculated the point prevalence of STIC. Results: We enrolled 280 patients. Of these, 107 (38.2%) and 173 (61.8%) underwent respectively total and partial bilateral salpingectomy. Majority of CDs were elective (81.8%); we did not find differences for intra- and post-operative surgical procedure-related complications. Bilateral fimbriated-part of the tube was available for analysis in 245 patients and STIC was identified in only one patient (prevalence of 0.4%). Conclusions: The frequency of STIC in patients undergoing partial or total bilateral salpingectomy during CD is extremely low, less than 1%. Total bilateral salpingectomy can be proposed as post-partum permanent contraception procedure without increasing surgical related complications. Further randomised studies are needed to confirm the benefits and safety of this procedure.